دور راس المال الفكري في تعزيز ريادة الأعمال - خديجة شنتوف (university of eloued جامعة الوادي, 2025)
"ملخص: هدفت هذه الدراسة إلى استكشاف ما مدى تأثير أبعاد رأس المال الفكري في تعزيز ريادة الأعمال، بمؤسسة اتصالات الجزائر بالوادي. ولقد تم اعتماد المنهج الوصفي التحليلي واستخدام استبيان وزع على عينة تتكون من 40 موظف لتحليل آرائهم، وتمت معالجة البيانات باستخدام تحليل الاستبيان، وأظهرت النتائج وجود علاقة إيجابية بين مكونات رأس المال الفكري وريادة الأعمال، كما تبين أن المؤسسة تولي اهتماماً معتبراً بالبنية التنظيمية والمعلوماتية، في حين تحتاج إلى مزيد من الجهود في مجالي تنمية الكفاءات البشرية وتعزيز الشراكات الخارجية، وأوصت الدراسة بأهمية الاستثمار في المعرفة وتفعيل ثقافة الإبداع لدعم الريادة وتحقيق الاستدامة داخل المؤسسة. "Summary: This study aimed to explore the extent to which intellectual capital influences entrepreneurship in Algeria's El Oued Telecommunications Corporation. Descriptive principles of new analysis were used to create a questionnaire distributed to 40 employees to analyze their opinions. Data was obtained using questionnaire analysis, demonstrating a positive relationship between the components of intellectual capital and entrepreneurship. It also helped the corporation pay significant attention to the creative structure, while requiring expertise in the field of professional competency development and professional partnerships. The study recommended the importance of investing in knowledge and the effectiveness of innovation leadership in sustainability within the organization.
ماستر علوم التجارية
Keywords: رأس مال فكري; ريادة أعمال; تصالات الجزائر; الترميز الاقتصادي (JEL; intellectual capital; entrepreneurship; Algeria telecom. Economic coding (JEL): L83- O15-O34